Racial dissimilarity and diversity climate effect organizational identification. Issue 5 (20th June 2016) - Cole, Brooklyn; Jones, Raymond J.; Russell, Lisa M.
Abstract : Purpose: The purpose of this paper is to empirically examine the relationship between psychological diversity climate (PDC) and organizational identification (OID) when influenced by racial dissimilarity between the subordinate and supervisor. Design/methodology/approach: Ordinary least squares hierarchical regression analysis was run for hypotheses testing. Findings: Three of the four hypothesized relationships were supported. Support was found for the direct relationship between PDC and OID. The moderator race was significant thus also supported. The moderator of dissimilarity was not supported. Finally the three-way interaction with race and dissimilarity was supported. Practical implications: OID is an important variable for overall organizational success. OID influences a wealth of organizationally relevant outcomes including turnover intentions. Considering higher turnover exists for minority employees, understanding how diversity climate perceptions vary by employee race and therefore impact OID differently, helps managers when making decisions about various initiatives. Originality/value: This study is the first the authors know of to investigate the impact of dissimilarity on the PDC-OID relationship.